2017
DOI: 10.1515/agr-2017-0001
|View full text |Cite
|
Sign up to set email alerts
|

Reed Biomass, a Possibility of Cultivation and Protection of “Wetland” in Korça Field in Albania

Abstract: The human society since early times has utilized the fire as a mean to accomplish its own needs and fuel providing has always been its main concern. In the framework of the environmental and forestry protection increasingly is required the retrievable and sustainable alternative energy. The utilization of reed biomass is an alternative of the retrievable biomass. The world is using since many years the reed biomass as fuel source. Whereas in Albania the utilization of the reed biomass has been observes only in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 3 publications
1
5
0
Order By: Relevance
“…Based on the different quality attributes SI range of 0.046 to 0.026; 0.041 to 0.024 and 0.041 to 0.026 were presumed to be optimal ranges for harvesting Gala Redlum (V1), Red Velox and Super Chief apples grown under temperate conditions of Kashmir in North Western Himalayas when intended for fresh consumption. Icka and Damo (2014) also reported that Streif index decreased from 0.35 to 0.04 when harvesting was prolonged from first to third harvesting date in apples. Icka and Damo (2014) recommended SI range of 0.075 to 0.10 for optimum harvesting of Red Delicious apples in Korca region.…”
Section: Resultsmentioning
confidence: 88%
See 3 more Smart Citations
“…Based on the different quality attributes SI range of 0.046 to 0.026; 0.041 to 0.024 and 0.041 to 0.026 were presumed to be optimal ranges for harvesting Gala Redlum (V1), Red Velox and Super Chief apples grown under temperate conditions of Kashmir in North Western Himalayas when intended for fresh consumption. Icka and Damo (2014) also reported that Streif index decreased from 0.35 to 0.04 when harvesting was prolonged from first to third harvesting date in apples. Icka and Damo (2014) recommended SI range of 0.075 to 0.10 for optimum harvesting of Red Delicious apples in Korca region.…”
Section: Resultsmentioning
confidence: 88%
“… Icka and Damo (2014) also reported that Streif index decreased from 0.35 to 0.04 when harvesting was prolonged from first to third harvesting date in apples. Icka and Damo (2014) recommended SI range of 0.075 to 0.10 for optimum harvesting of Red Delicious apples in Korca region.…”
Section: Resultsmentioning
confidence: 88%
See 2 more Smart Citations
“…Four possible revenue sources have been considered for comparative purposes: directly selling reeds ($70 per t), 95,96 biorefinery for bioethanol production ($420-1000 per t), 96,97 biorefinery for cellulose pulp production ($450-900 per t), 96,98 and production of reed pellets for fuel use ($140 per t). 95,99 All revenue options are heavily dependent on the achievable profit margin, which will vary with the scale of operation. As a result, thorough analysis into the process economics of each route and market size is required, which has been considered beyond the scope of this study.…”
Section: Environmental Science: Water Research and Technology Papermentioning
confidence: 99%